2008
DOI: 10.2174/138527208786786282
|View full text |Cite
|
Sign up to set email alerts
|

Solenostemma argel: A Rich Source of Very Unusual Pregnane and 14,15- Secopregnane Glycosides with Antiproliferative Activity

Abstract: Solenostemma argel Hayne (Asclepiadaceae) is an Egyptian plant whose leaves are commonly used in traditional medicine as a purgative, antipyretic and antispasmodic remedy. From the pericarps, hairy seeds and leaves fifteen new 14,15-secopregnane glycosides, namely argelosides A-J, and nine new 15-ketopregnane glycosides, namely stemmosides C-K, have been isolated. Argelosides A-J show very unusual structures characterized by the opening of ring D between C-14 and C-15, and the occurrence of two ketal functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The 21 skeletal signals in the 13 C NMR spectrum were classified by the DEPT and HSQC spectra into two methyls, six methylene groups, two alkyl methines, three quaternary alkyl carbons, six oxygenated carbons (including two primary, three secondary and one tertiary), and a trisubstituted double bond. This suggested that compound 2 is a 3-oxy-4-en-14,15-secopregnane derivative (Plaza et al, 2003, 2005; Perrone et al, 2006, 2008). In the COSY spectrum, the oxygenated methine proton at δ H 4.56 (1H, t, J = 4.5 Hz, H-16) showed correlations with an alkyl methine proton at δ H 2.60 (1H, dd, J = 7.6, 4.4 Hz, H-17) and one geminal proton of an oxygenated methylene at δ H 4.02 (1H, dd, J = 10.0, 4.4 Hz, H a -15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 21 skeletal signals in the 13 C NMR spectrum were classified by the DEPT and HSQC spectra into two methyls, six methylene groups, two alkyl methines, three quaternary alkyl carbons, six oxygenated carbons (including two primary, three secondary and one tertiary), and a trisubstituted double bond. This suggested that compound 2 is a 3-oxy-4-en-14,15-secopregnane derivative (Plaza et al, 2003, 2005; Perrone et al, 2006, 2008). In the COSY spectrum, the oxygenated methine proton at δ H 4.56 (1H, t, J = 4.5 Hz, H-16) showed correlations with an alkyl methine proton at δ H 2.60 (1H, dd, J = 7.6, 4.4 Hz, H-17) and one geminal proton of an oxygenated methylene at δ H 4.02 (1H, dd, J = 10.0, 4.4 Hz, H a -15).…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of 14,15-secopregnane derivatives with similar polyoxygenated features to 2 is rare in the plant kingdom, and other naturally occurring compounds of this class have been found from a limited number of plants such as species in the genera Cynanchum and Solenostemma of the family Asclepiadaceae, and the genus Mandevilla of the family Apocynaceae (Kennard et al, 1968; Lavault et al, 1999; Chen et al, 2008; Plaza et al, 2003, 2005; Perrone et al, 2006, 2008; Niero et al, 1999, 2002; Yunes et al, 1993). These compounds are characterized by the cleavage of the D ring between C-14 and C-15, a hexahydrofuro[3,4- b ]furan ring on ring C, with C-20 connected to C-14 or C-18 through an oxygen atom, to generate ketal groups at C-14 and/or C-20.…”
Section: Resultsmentioning
confidence: 99%
“…The 17α configuration was also confirmed by the observation that the carbonyl carbon of an α-linked methyl ketone at C-17 appears at δ 209.2, 209.3 and 214.5 ppm for the aglycones 6 , 7 and 8 , respectively, and at 214.4 ppm for the steroidal glycoside 3 , when compared with δ 217 ppm for the β configuration (Table 1 ). 17-Epimers having an α-oriented side chain were isolated from the twigs of Pergularia pallida (Khare et al 1984 ), the roots of Cynanchum wilfordii Hemsley (Tsukamoto et al 1985 ), the roots of Calotropis gigantea Dryand (Shibuya et al 1992 ), the roots of Cynanchum caudatum M. (Warashina and Noro 1995 ), the aerial part of Asclepias incarnata L. (Warashina and Noro 2000 ), the roots of Cynanchum auriculatum Royle ex Wight (Xhang et al 2000 ), the aerial parts of Cynanchum aphyllum L. (Kanchanapoom et al 2002 ), the stem of Marsdenia tenacissima (Deng et al 2005 ), and from the pericarps, hairy seeds and leaves of Solenostemma argel Hayne (Perrone et al 2008 ), the roots of Asclepias curassavica L. (Warashina and Noro 2008 ), the roots of Asclepias syriaca L. (Warashina and Noro 2009 ) (all of which species belong to the Asclepiadaceae family), and from Nerium oleander (Bai et al 2007 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Hegazi et al (2006) investigated the hepatotoxic and nephrotoxic effect of S. argel. The plant also showed significant anti-cancer and antioxidant activities (Nassr-Allah et al, 2009 andHanafi andMansour, 2011) Phytochemical investigations on S. argel have led to the isolation of compounds belonging to several classes of secondary metabolites, such as flavonoid glycosides (El-Askary, 2003 andHeneidak et al, 2006), monoterpenes (Kamel et al, 2000 andEl-Askary, 2003), acylated phenolic glycosides (Kamel, 2003), pregnane and secopregnane glycosides (Hamed, 2001;Hassan et al, 2001;El-Askary, 2003;Plaza et al, 2003, 2004, 2005a& b and Perrone et al, 2006. The pharmacological studies on S. argel evidenced spasmolytic and anaesthetic (El-Tahir et al, 2005), fungitoxic Ouf, 1993 andAbd El-Hady et al, 1994a &b) and antimicrobial activity against selected gram-positive and gramnegative bacteria (Hegazi et al, 1994 andTharib et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen new 14,15-secopregnane glycosides, namely argelosides A-J, and nine new 15-ketopregnane glycosides, namely stemmosides C-K, have been isolated from the pericarps, hairy seeds and leaves (Perrone et al, 2008). Kaempferol, kaempferol monoglycoside, and its derivatives, isolated along with other flavonoids from a preparation of the S. argel, were found to have a potent spasmolytic activity (Khalid et al, 1992).…”
Section: Introductionmentioning
confidence: 99%